2013
DOI: 10.1089/jop.2012.0175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ocular and General Safety Following Repeated Dosing of Dexamethasone Phosphate Delivered by Transscleral Iontophoresis in Rabbits

Abstract: The results of this investigation suggest that repeated transscleral iontophoresis with dexamethasone phosphate may be safe for use as a treatment for inflammatory ocular disorders that require prolonged and/or repeated corticosteroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Although only the 25% DSP group showed statistically significant reduction in body weight, the consistent decline in body weights of the animals in these two groups indicate that long-term exposure at these levels of DSP-Visulex dosing (i.e., 15 and 25% DSP for 20 minutes) may have significant systemic side effects on rabbit. Since all animals exhibited systemic exposure of both DSP and DEX after single administration of the DSP-Visulex (discussed above), this is an expected outcome after multiple treatments of DSP-Visulex for 3 months [42,43]. It should be noted that the 20-minute treatment duration and 25% DSP tested in this study were an exaggerated wearing time and concentration to find the adverse effect (if any).…”
Section: Ocular Toxicity Of Dsp-visulex In Animalmentioning
confidence: 68%
“…Although only the 25% DSP group showed statistically significant reduction in body weight, the consistent decline in body weights of the animals in these two groups indicate that long-term exposure at these levels of DSP-Visulex dosing (i.e., 15 and 25% DSP for 20 minutes) may have significant systemic side effects on rabbit. Since all animals exhibited systemic exposure of both DSP and DEX after single administration of the DSP-Visulex (discussed above), this is an expected outcome after multiple treatments of DSP-Visulex for 3 months [42,43]. It should be noted that the 20-minute treatment duration and 25% DSP tested in this study were an exaggerated wearing time and concentration to find the adverse effect (if any).…”
Section: Ocular Toxicity Of Dsp-visulex In Animalmentioning
confidence: 68%
“…Iontophoresis is a well‐known drug‐delivery strategy and has been used in ophthalmology for decades . It consists in transferring charged molecules to a target tissue through the application of a low‐intensity electric field and has been shown to be safe both in ex vivo and in vivo studies . Current densities up to 4.0 mA/cm 2 for 10 min through the sclera of rabbits have been shown to cause no alterations to eye function or structure .…”
Section: Discussionmentioning
confidence: 99%
“…20 Importantly, preclinical studies showed that iontophoresis employing low-current densities is safe and does not induce pathological structural changes in the cornea. [21][22][23][24] Ocular iontophoresis has also been explored as a delivery mode for iodide to treat dry eye 25,26 and for 6-hydroxydopamine to treat glaucoma, 27 but these applications did not advance into clinical practice. 27 Iontophoresis has only more recently become accepted by the clinical community as a promising technique for facilitating ocular delivery.…”
Section: Iontophoresis Technologymentioning
confidence: 99%
“…29 Further, biweekly trans-scleral iontophoresis of dexamethasone phosphate solution at current doses of 10, 14, and 20 mA-min over 24 weeks appeared safe in rabbits, with no treatment-related effects on intraocular pressure (IOP), electroretinography, or any histopathology. 24 The therapeutic use of an iontophoresis device (EyeGate Pharmaceuticals, Inc., Waltham, MA) to deliver a corticosteroid was initially explored clinically in 17 patients who experienced active graft rejection after a penetrating keratoplasty. 23 Iontophoretic applications of 62.5 mg/mL methylprednisolone sodium succinate were delivered once a day over 3 consecutive days using an electric current of 1.5 mA for 4 min.…”
Section: Evolution Of Trans-scleral Corticosteroid Delivery Using Ionmentioning
confidence: 99%